ChemInform Abstract: Mixed Bioengineering—Chemical Synthesis Approach for the Efficient Preparation of Δ7‐Dafachronic Acid. Issue 42 (14th October 2014) - Kinzurik, Matias I.; Hristov, Lachezar V.; Matsuda, Seiichi P. T.; Ball, Zachary T.
Abstract The steroidal hormone Δ7‐dafachronic acid is prepared in 4 steps, including an olefin metathesis.